2021
DOI: 10.1186/s12879-021-06375-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and genetic diversity of norovirus among hospitalized children with acute gastroenteritis in Tianjin, China, 2018–2020

Abstract: Background Norovirus (NoV) is a major cause of viral acute gastroenteritis (AGE) in children worldwide. Epidemiological analysis with respect to the virus strains is limited in China. This study aimed to investigate the prevalence, patterns, and molecular characteristics of NoV infection among children with AGE in China. Methods A total 4848 stool samples were collected from children who were admitted with AGE in Tianjin Children’s Hospital from Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Thus, the current study first reported that the overall detection rate of norovirus was 26.1% in children under five years old from 2018 to 2020 in Southwest China. The detection rate was similar to some hospital-based sentinel surveillances for norovirus diarrhea in other regions of China, while was higher than the globally norovirus incidence (about 20%) [ 14 , 18 , 24 ]. Regional differences in norovirus in China are also noteworthy, and norovirus was more prevalent in North China than in South China [ 21 , 24 ].…”
Section: Discussionsupporting
confidence: 80%
“…Thus, the current study first reported that the overall detection rate of norovirus was 26.1% in children under five years old from 2018 to 2020 in Southwest China. The detection rate was similar to some hospital-based sentinel surveillances for norovirus diarrhea in other regions of China, while was higher than the globally norovirus incidence (about 20%) [ 14 , 18 , 24 ]. Regional differences in norovirus in China are also noteworthy, and norovirus was more prevalent in North China than in South China [ 21 , 24 ].…”
Section: Discussionsupporting
confidence: 80%
“…Non-GII.4 genotypes, peak and ebb in prevalence [113,123,140]. GII.3, GII.6, GII.2, GII.12 and GII.17 are frequently detected [123,[141][142][143]. GI.3 is the most frequently detected GI genotype [122,123].…”
Section: Virus Backgroundmentioning
confidence: 99%
“…Capsid genes commonly circulate with interchangeable polymerase types, as recombinant viruses [144]. The difference in virulence between recombinant viruses compared to non-recombinant viruses is under investigation but hampered by the lack of tools for evaluation [141,[145][146][147][148]. Co-infection with other AGE viruses, bacteria and parasites are also common and understudied [137,[149][150][151].…”
Section: Virus Backgroundmentioning
confidence: 99%
“…Acute diarrheal diseases ranked seventh among the reasons of mortality in LMIC in the international disorder burden collection, 2013, with an envisioned 1. Three million deaths (2 Four %).1 Most of those deaths arise in kids under the age of 5 years in LMIC and diarrhea stays among the top 5 causes of all deaths among children more youthful than age 5 years, as tabulated in 2013 [11][12][13][14][15][16][17][18][19][20].…”
Section: Acute Diarrheamentioning
confidence: 99%